2015
DOI: 10.1007/s11948-015-9628-2
|View full text |Cite
|
Sign up to set email alerts
|

The Acid Test for Biological Science: STAP Cells, Trust, and Replication

Abstract: In January 2014, a letter and original research article were published in Nature describing a process whereby somatic mouse cells could be converted into stem cells by subjecting them to stress. These "stimulus-triggered acquisition of pluripotency" (STAP) cells were shown to be capable of contributing to all cell types of a developing embryo, and extra-embryonic tissues. The lead author of the publications, Haruko Obokata, became an overnight celebrity in Japan, where she was dubbed the new face of Japanese s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Individuals involved in the disease have excessive expectations for the effect of regenerative medicine on agerelated macular degeneration; therefore, current television-centered information acquisition may be insufficient. With the example of issues related to Stimulus-Triggered Acquisition of Pluripotency (STAP) cells [6], scientific news reporting via television tends to prioritize sensationalism over accurate scientific information. A previous study reported that there is no association between information acquisition via television and scientific knowledge, although information acquisition via the Internet is associated with scientific knowledge [7].…”
Section: Discussionmentioning
confidence: 99%
“…Individuals involved in the disease have excessive expectations for the effect of regenerative medicine on agerelated macular degeneration; therefore, current television-centered information acquisition may be insufficient. With the example of issues related to Stimulus-Triggered Acquisition of Pluripotency (STAP) cells [6], scientific news reporting via television tends to prioritize sensationalism over accurate scientific information. A previous study reported that there is no association between information acquisition via television and scientific knowledge, although information acquisition via the Internet is associated with scientific knowledge [7].…”
Section: Discussionmentioning
confidence: 99%
“…Where such data were lacking, secondary sources were vetted and compiled [23,27-29]. All data obtained were used and reported according to the terms and privacy policies of the respective data sources.…”
Section: Methodsmentioning
confidence: 99%
“…The 2014 Obokata paper is one of two papers retracted in Nature that are first-authored by stem cell researcher Haruko Obokata, which initially elicited much interest and excitement that rapidly spiraled downwards into a dramatic case of misconduct [36,37]. In what might be called the stimulus-triggered acquisition of pluripotency (STAP) cells affair, the purported findings of somatic cells being readily reprogrammed into pluripotent stem-cell-like states in an acidic bath were quickly shown to be irreproducible by others eager to verify the phenomenon, and ultimately failed to be replicated even by the authors themselves [38,39].…”
Section: Qualitative Analysis Of Five Papers With High Percentages Of...mentioning
confidence: 99%